Optical laminate
By using a multi-layer liquid crystal oriented fixed layer structure and an oriented substrate with high tensile elastic modulus in the optical laminate, the peeling defect problem of the optical laminate when peeling the substrate in the prior art is solved, and the optical laminate is realized Thinning and stability improvement.
Patent Information
- Application Number
- CN202411036614.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The conventional optical laminate is prone to peeling off the oriented substrate when peeling off the conventional optical laminate, resulting in the liquid crystal film being peeled off together.
An optical laminate structure including a liquid crystal orientation fixing layer is adopted, wherein the retardation layer is composed of first and second liquid crystal orientation fixing layers, the first liquid crystal orientation fixing layer is laminated on the polarizer through a first adhesive layer, and the second liquid crystal orientation is The fixing layer is laminated on the retardant layer in a peelable manner and an oriented substrate with a high tensile elastic modulus is used.
The peeling defects during the peeling of the substrate are effectively suppressed, and the liquid crystal oriented fixing layer is prevented from peeling off with the substrate, thereby achieving significant thinning and improving stability of the optical laminate.
Smart Images

Figure CN119439348A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical laminate. Background Art
[0002] In recent years, image display devices (e.g., organic EL display devices or inorganic EL display devices), typified by liquid crystal display devices and electroluminescent (EL) display devices, have rapidly gained wider applications. In an image display device, an optical laminate including a retardation film (e.g., an antireflection film obtained by integrating a polarizer and a retardation film with each other) has been used in many cases. In recent years, with the increasing demand for thinning of image display devices, the demand for thinning of optical laminates has also increased. To thin the optical laminate, progress has been made in thinning the retardation layer (retardation film) that contributes significantly to the thickness. A typical example of a retardation thin film is a film obtained by aligning a liquid crystal compound and fixing the alignment state (hereinafter referred to as a "liquid crystal film"). The birefringence (Δn) of the liquid crystal compound is much larger than that of the resin, so the thickness of the liquid crystal film used to obtain a desired in-plane retardation can be much smaller than the thickness of the stretched film of the resin film. The liquid crystal film is usually formed by applying a composition containing a liquid crystal compound to an alignment substrate and curing or solidifying the applied film. The formed liquid crystal film is bonded to a polarizer, and then the alignment substrate is peeled off and removed. However, when the liquid crystal film is used for a thin polarizer, peeling defects may occur when the alignment substrate is peeled off. Specifically, when the alignment substrate is peeled off, the liquid crystal film may also be peeled off together. Summary of the Invention
[0003] The present invention has been made to solve the above problems of the prior art, and the main object of the present invention is to provide an optical laminate including a liquid crystal alignment fixing layer and suppressing peeling defects when peeling off the alignment substrate.
[0004] According to at least one embodiment of the present invention, there is provided an optical laminate including: a polarizer including a polarizer; a retardation layer laminated on the polarizer via a first adhesive layer; and a substrate laminated on the retardation layer in a peelable manner. The retardation layer includes, in order from the polarizer side, a first liquid crystal alignment fixing layer and a second liquid crystal alignment fixing layer laminated on the first liquid crystal alignment fixing layer via a second adhesive layer; and has, as a whole, one of a circular polarization function or an elliptical polarization function, a relationship of Re(450)<Re(550)<Re(650), and an Nz coefficient of 0.30 to 0.70. The substrate is an alignment substrate for the second liquid crystal alignment fixing layer and has a tensile elastic modulus of 3,000 N / mm 2 or more.
[0005] In the above item [1], the substrate has a thickness of 75 μm or more.
[0006] In the above item [1] or [2], the substrate is a single-layer film.
[0007] In the above item [1] or [2], the substrate has a laminate structure of two or more layers.
[0008] In any one of the above items [1] to [4], the polarizing plate further includes a protective layer disposed on both sides of the polarizer and having a thickness of 100 μm or less.
[0009] In any one of the above items [1] to [5], the total thickness from the polarizing plate to the second liquid crystal alignment fixing layer is 110 μm or less.
[0010] In any one of the above items [1] to [6], the first adhesive layer is formed of a UV-curable adhesive.
[0011] According to at least one embodiment of the present invention, an optical laminate including a liquid crystal alignment fixing layer and in which peeling defects are suppressed when an alignment substrate is peeled can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is a schematic cross-sectional view of an optical stack according to at least one embodiment of the present invention. DETAILED DESCRIPTION
[0013] Typical embodiments of the present invention are described below. However, the present invention is not limited thereto.
[0014] (Definition of terms and symbols)
[0015] Definitions of terms and symbols used herein are as follows.
[0016] (1) Refractive index (nx, ny and nz)
[0017] “nx” represents the refractive index in the direction of maximum in-plane refractive index (i.e., slow axis direction), “ny” represents the refractive index in the direction perpendicular to the slow axis in the plane (i.e., fast axis direction), and “nz” represents the refractive index in the thickness direction.
[0018] (2) In-plane retardation (Re)
[0019] "Re(λ)" refers to the in-plane retardation of a film measured with light having a wavelength of λ nm at 23° C. For example, "Re(550)" refers to the in-plane retardation of a film measured with light having a wavelength of 550 nm at 23° C. When the thickness of the film is represented by "d" (nm), Re(λ) is determined by the equation "Re=(nx-ny)×d".
[0020] (3) Thickness direction retardation (Rth)
[0021] "Rth(λ)" refers to the thickness direction retardation of the film measured at 23°C using light having a wavelength of λnm. For example, "Rth(550)" refers to the thickness direction retardation of the film measured at 23°C using light having a wavelength of 550nm. When the thickness of the film is represented by "d" (nm), rth(λ) is determined by the equation "Rth = (nx-nz) × d".
[0022] (4) Nz coefficient
[0023] The Nz coefficient is determined according to the equation "Nz = Rth / Re".
[0024] (5) Angle
[0025] When an angle is referred to herein, the angle includes angles in both the clockwise and counterclockwise directions unless otherwise specified.
[0026] A. Optical laminate
[0027] Figure 1 is a schematic cross-sectional view of an optical laminate according to at least one embodiment of the present invention. The optical laminate 100 of the illustrated example includes: a polarizer 10; a delay layer 20 laminated on the polarizer 10 through a first adhesive layer 30; and a substrate 40 laminated on the delay layer 20 in a releasable manner. The polarizer 10 generally includes a polarizer 11 and protective layers 12 and 13 disposed on both sides of the polarizer 11. Depending on the purpose, at least one of the protective layers 12 and 13 can be omitted. Therefore, the polarizer can be a so-called double-sided protected polarizer or a so-called single-sided protected polarizer, or can be formed by a polarizer alone. The polarizer is preferably a double-sided protected polarizer, and the thickness of the polarizer is, for example, 110 μm or less, preferably 100 μm or less, and more preferably 15 μm to 100 μm. By adopting a double-sided protection structure as the structure of the polarizer and setting the thickness to a specific value or less, the effect according to the embodiment of the present invention can be made significant.
[0028] The retardation layer 20 includes, in order from the polarizer 10 side, a first liquid crystal alignment fixing layer 21 and a second liquid crystal alignment fixing layer 22 laminated on the first liquid crystal alignment fixing layer 21 via a second adhesive layer 25. When the liquid crystal alignment fixing layer is used as the retardation layer, the desired in-plane retardation can be achieved with a thickness much smaller than that of the stretched film of the resin film. As a result, a significant thinning of the optical laminate can be achieved. The retardation layer 20 as a whole has a circular polarization function or an elliptical polarization function, the relationship of Re(450) < Re(550) < Re(650), and an Nz coefficient of 0.30 - 0.70 (as a laminate of the first liquid crystal alignment fixing layer 21 and the second liquid crystal alignment fixing layer 22). According to at least one embodiment of the present invention, in the optical laminate including such a specific retardation layer, peeling defects during peeling of the substrate can be suppressed. As used herein, the term "liquid crystal alignment fixing layer" refers to the following layer: the liquid crystal compound is aligned in the layer in a predetermined direction, and its alignment state is fixed. The term "liquid crystal alignment fixing layer" is a concept including an alignment cured layer obtained by curing a liquid crystal monomer.
[0029] The substrate 40 is an alignment substrate for the second liquid crystal alignment fixing layer 22. That is, by applying a liquid crystal composition for forming the second liquid crystal alignment fixing layer onto the substrate 40, the liquid crystal compound in the composition is aligned by the alignment regulating force of the substrate 40, and the liquid crystal compound in the aligned state is cured or hardened to form the second liquid crystal alignment fixing layer 22. The laminate of the substrate 40 and the second liquid crystal alignment fixing layer 22 is laminated on the polarizer (in the illustrated example, the first liquid crystal alignment fixing layer 21 is laminated on the polarizer 10). When producing the optical laminate as the final product, the substrate 40 can usually be peeled off and removed. That is, the substrate 40 is laminated on the second liquid crystal alignment fixing layer 22 in a peelable manner. In at least one embodiment of the present invention, the tensile elastic modulus of the substrate 40 is 3,000 N / mm 2 or more. With this configuration, peeling defects during peeling of the substrate can be suppressed. Specifically, peeling of the second liquid crystal alignment fixing layer together with the substrate can be prevented or satisfactorily suppressed. The first liquid crystal alignment fixing layer 21 is also formed and laminated on the polarizer in the same manner as described above, so the same substrate as the substrate 40 is preferably used as the alignment substrate for the first liquid crystal alignment fixing layer 21.
[0030] In the optical laminate, the total thickness from the polarizer to the second liquid crystal alignment fixing layer (i.e., the part that can be used as the final product) is, for example, 120 μm or less, preferably 110 μm or less, and more preferably 20 μm to 110 μm. Although peeling defects are significant when peeling the substrate of such an extremely thin optical laminate, according to at least one embodiment of the present invention, such peeling defects can be suppressed.
[0031] The components of the optical laminate are specifically described below.
[0032] B. Polarizer
[0033] B-1. Polarizer
[0034] The polarizer 11 is generally formed of a polyvinyl alcohol (PVA)-based resin film containing a dichroic substance such as iodine. Examples of the PVA-based resin include polyvinyl alcohol, partially fixed polyvinyl alcohol, vinyl alcohol copolymers, and partially saponified products based on ethylene-vinyl acetate copolymers.
[0035] The resin based on PVA preferably includes the resin based on PVA modified by acetoacetyl. Utilize this structure, can obtain the polarizer with required mechanical strength. When the total amount of the resin based on PVA is limited to 100wt%, the blending amount of the resin based on acetoacetyl modified PVA is preferably 5wt% to 20wt%, more preferably 8wt% to 12wt%. When the blending amount falls within such a range, there is a polarizer with more excellent mechanical strength.
[0036] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as "halide"). Examples of iodides include potassium iodide, sodium iodide and lithium iodide. The content of halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, relative to 100 parts by weight of PVA-based resin. In the manufacturing method described later, the halide is mixed into a coating liquid for forming a PVA-based resin layer used as a precursor of the polarizer, and can be finally introduced into the polarizer. When the halide is introduced into the polarizer, the orientation properties of the PVA molecules in the polarizer can be improved, and thus a polarizer with excellent optical properties (usually, high polarization degree and high single-layer transmittance are obtained at the same time) can be obtained.
[0037] The polarizer preferably exhibits absorption dichroism at any wavelength within the wavelength range of 380nm to 780nm. The monolayer transmittance of the polarizer is preferably 41.0% to 46.0%, more preferably 42.0% to 45.0%. The polarization degree of the polarizer is preferably 97.0% or higher, more preferably 99.0% or higher, and even more preferably 99.9% or higher. According to at least one embodiment of the present invention, even when the monolayer transmittance falls within the above range, the polarization degree can be maintained within such a range.
[0038] The thickness of the polarizer is, for example, 12 μm or less, preferably 10 μm or less, more preferably 1 μm to 8 μm, and further preferably 3 μm to 7 μm. The combination of such a thin polarizer and a liquid crystal orientation fixing layer makes the optical laminate significantly thinner. In addition, when the thickness of the polarizer falls within the above range, the curling of the polarizer when heated can be satisfactorily suppressed, and its satisfactory appearance durability when heated can be obtained.
[0039] The polarizer can be produced by any appropriate method. For example, the resin film used to form the polarizer may be a single-layer resin film or may be a laminate of two or more layers.
[0040] Specific examples of the polarizer formed of a single-layer resin film include a polarizer formed of a hydrophilic polymer film, such as a PVA-based film, a partially formalized PVA-based film, and a partially saponified film based on ethylene-vinyl acetate copolymer, which has been subjected to a dyeing treatment and a stretching treatment with a dichroic substance (such as iodine or a dichroic dye), and a polarizer based on an oriented film of a polyene, such as a dehydrated product of PVA and a dehydrochlorinated product of polyvinyl chloride. It is preferable to use a polarizer obtained by dyeing a PVA-based film with iodine and uniaxially stretching it, because such a polarizer has excellent optical characteristics.
[0041] Iodine dyeing is performed by, for example, immersing the film based on PVA in an aqueous solution of iodine. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. Stretching can be performed after the dyeing process, or can be performed while dyeing. In addition, dyeing can be performed after stretching. As required, swelling treatment, cross-linking treatment, washing treatment, drying treatment, etc. are performed to the film based on PVA. For example, when washing the film based on PVA with water by immersing in water before dyeing, pollutants and anti-blocking agents on the film surface based on PVA can be washed off, and in addition, the film based on PVA can be swollen to prevent uneven dyeing, etc.
[0042] A specific example of a polarizer obtained by using a laminate is a laminate using a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate or a laminate of a resin substrate and a PVA-based resin layer formed by coating on a resin substrate. The polarizer obtained by using a resin substrate and a laminate of a PVA-based resin layer formed by coating on a resin substrate can be prepared, for example, by applying a PVA-based resin solution to a resin substrate; drying the solution to form a PVA-based resin layer on a resin substrate, thereby providing a laminate of a resin substrate and a PVA-based resin layer; and stretching and dyeing the laminate to convert the PVA-based resin layer into a polarizer. In at least one embodiment of the present invention, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching generally includes stretching the laminate in a state where the laminate is immersed in a boric acid aqueous solution. In addition, stretching may also include stretching the laminate in air at a high temperature (e.g., 95° C. or higher) before stretching in a boric acid aqueous solution as required. In addition, in at least one embodiment of the present invention, it is preferred to subject the laminate to a drying shrinkage treatment, which includes heating the laminate while conveying the laminate in its length direction to shrink the laminate by 2% or more in its width direction. The production method of at least one embodiment of the present invention typically includes subjecting the laminate to an auxiliary stretching treatment in air, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in the order described. When auxiliary stretching is adopted, the crystallinity of PVA can be improved even when PVA is applied to a thermoplastic resin, and thus high optical properties can be achieved. In addition, when the orientation properties of PVA are improved in advance while improving the crystallinity, when the laminate is immersed in water in a subsequent dyeing step or a stretching step, problems such as a decrease in the orientation properties of PVA and its dissolution can be prevented, and thus high optical properties can be achieved. In addition, compared with the case where the PVA-based resin layer does not contain any halide, the interference with the orientation of the polyvinyl alcohol molecules and the decrease in their orientation properties can be suppressed compared with the case where the PVA-based resin layer does not contain any halide. Therefore, the optical properties of the polarizer obtained by the treatment step (e.g., dyeing treatment and underwater stretching treatment) carried out by immersing the laminate in a liquid can be improved. In addition, the optical properties can be improved by shrinking the laminate in its width direction through a drying shrinkage treatment. The laminate of the resulting resin substrate and polarizer can be used as it is (i.e., the resin substrate can be used as a protective layer for the polarizer), or can be used by laminating any suitable protective layer on the peeling surface of the laminate of the resin substrate and the polarizer from which the resin substrate has been peeled off, or laminating on the surface on the opposite side of the peeling surface according to the purpose.Details on such a method of producing a polarizer are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580 and Japanese Patent No. 6470455, the descriptions of which are incorporated herein by reference in their entirety.
[0043] B-2. Protective layer
[0044] The protective layers 12 and 13 are each formed of any appropriate resin film. The material used to form the resin film is generally, for example, a cellulose-based resin (such as triacetyl cellulose (TAC)), a cycloolefin-based resin (such as polynorbornene), a (meth) acrylic resin, a polyester-based resin (such as polyethylene terephthalate (PET) or polyethylene naphthalate (PEN)), a polyolefin-based resin (such as polyethylene) or a polycarbonate-based resin. A typical example of a (meth) acrylic resin is a (meth) acrylic resin having a lactone ring structure. The (meth) acrylic resin having a lactone ring structure is described in, for example, Japanese Patent Application Laid-Open No. 2000-230016, Japanese Patent Application Laid-Open No. 2001-151814, Japanese Patent Application Laid-Open No. 2002-120326, Japanese Patent Application Laid-Open No. 2002-254544 and Japanese Patent Application Laid-Open No. 2005-146084, which are incorporated herein by reference. Among them, from the viewpoint of being easy to process into an irregular shape, for example, a cellulose-based resin is preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low moisture permeability and excellent durability, a cycloolefin resin and a (meth) acrylic resin are preferred.
[0045] The optical stack is usually arranged on the observer side of the image display device, and the protective layer 12 is usually arranged on its observer side. Therefore, the protective layer 12 needs to be surface treated as needed. Examples of surface treatment include hard coating treatment, anti-reflection treatment, anti-sticking treatment and anti-glare treatment. In addition / alternatively, when viewed through paired polarized sunglasses (usually imparting circular (elliptical) polarization function or imparting ultra-high delay), the protective layer 12 can be treated as needed to improve visibility. When such treatment is performed, excellent visibility can be achieved even when viewing the display screen through a polarized lens such as a paired polarized sunglasses. Therefore, the optical stack can even be suitably applied to an image display device that can be used outdoors.
[0046] In at least one embodiment of the present invention, the protective layer 13 is preferably optically isotropic. As used herein, the phrase "optically isotropic" means that the layer has an in-plane retardation Re(550) of 0nm to 10nm and a thickness direction retardation Rth(550) of -10nm to +10nm.
[0047] The thicknesses of the protective layers 12 and 13 are each preferably from 10 μm to 80 μm, more preferably from 12 μm to 40 μm, still more preferably from 15 μm to 35 μm. When the protective layer 12 is subjected to surface treatment, the thickness of the protective layer 12 is the thickness including the thickness of its surface treatment layer.
[0048] C. Delaying layer
[0049] As described above, the delaying layer 20 includes the first liquid crystal alignment fixing layer 21 and the second liquid crystal alignment fixing layer 22 in that order from the polarizer side. Further, as described above, the delaying layer 20 as a whole has a circular polarization function or an elliptical polarization function, the relationship of Re(450) < Re(550) < Re(650), and an Nz coefficient of 0.30 to 0.70 (as a laminate of the first liquid crystal alignment fixing layer 21 and the second liquid crystal alignment fixing layer 22). Regarding the description of the delaying layer in this section, when the delaying layer is simply referred to as the "delaying layer", the entire delaying layer is described, and when the delaying layer is simply referred to as the "liquid crystal alignment fixing layer", the first liquid crystal alignment fixing layer and the second liquid crystal alignment fixing layer are described together.
[0050] The Re(550) of the delaying layer 20 is preferably from 100 nm to 200 nm, more preferably from 120 nm to 190 nm, still more preferably from 130 nm to 180 nm, and particularly preferably from 150 nm to 170 nm. When the Re(550) of the delaying layer falls within such a range, the delaying layer can exhibit a satisfactory circular polarization function or elliptical polarization function in combination with a polarizer.
[0051] As described above, the delaying layer 20 has an Nz coefficient of 0.30 to 0.70. Accordingly, the delaying layer 20 exhibits a refractive index characteristic of nx > nz > ny. With this configuration, reflection in the tilting direction can be satisfactorily prevented, and an antireflection function can be exhibited over a wide viewing angle. The Nz coefficient is preferably from 0.35 to 0.65, more preferably from 0.40 to 0.60, still more preferably from 0.45 to 0.55.
[0052] The delaying layer 20 has the relationship of Re(450) < Re(550) < Re(650). That is, the delaying layer 20 preferably exhibits such reverse wavelength dispersion dependence that its retardation value increases as the wavelength of the measurement light increases. With this structure, a satisfactory antireflection function can be achieved in an extremely wide wavelength band. The ratio "Re(450) / Re(550)" is, for example, greater than 0.5 and less than 1.0, preferably from 0.7 to 0.95, more preferably from 0.75 to 0.92, still more preferably from 0.8 to 0.9. The ratio "Re(650) / Re(550)" is preferably 1.0 or greater and less than 1.15, more preferably from 1.03 to 1.1.
[0053] Examples of liquid crystal compounds for liquid crystal orientation fixed layers include liquid crystal polymers and liquid crystal monomers. Liquid crystal compounds are preferably polymerizable (i.e., liquid crystal monomers). When liquid crystal compounds are polymerizable, the arrangement state of the molecules of the liquid crystal compounds can be fixed by arranging the molecules of the liquid crystal compounds and then polymerizing the compounds. In this case, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal orientation fixed layer does not experience, for example, a transition to a liquid crystal phase, a glass phase, or a crystalline phase caused by a temperature change that is peculiar to the liquid crystal compound. As a result, the liquid crystal orientation fixed layer becomes a delay layer with excellent stability and is not affected by temperature changes.
[0054] In at least one embodiment of the present invention, the liquid crystal orientation fixing layer can be formed by using a composition containing a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). Herein, the "polymerizable liquid crystal compound" in the composition refers to a compound having a polymerizable group and having liquid crystal properties. A polymerizable group refers to a group that participates in a polymerization reaction, and is preferably a photopolymerizable group. Herein, a "photopolymerizable group" refers to a group that can participate in a polymerization reaction by, for example, an active free radical or acid generated by a photopolymerization initiator. For example, as described in Japanese Patent Translation Publication No. 2002-533742 (WO 00 / 37585A1), European Patent No. 358208 (U.S. Patent No. 5211877), European Patent No. 66137 (U.S. Patent No. 4388453), WO 93 / 22397A1, European Patent Application Publication No. 0261712, German Patent Application Publication No. 19504224, German Patent Application Publication No. 4408171, British Patent No. 2280445, etc., each can be used as a liquid crystal monomer. Specific examples of such polymerizable mesogen compounds include products available under the product name LC242 from BASF SE, products available under the product name E7 from Merck KGaA, and products available under the product name LC-Silicone-CC3767 from Wacker Chemie AG.
[0055] The expression mechanism of the liquid crystal properties of the liquid crystal compound may be thermotropic or lyotropic. In addition, the structure of the liquid crystal phase may be nematic liquid crystal or smectic liquid crystal. From the viewpoint of easy production, nematic liquid crystal having thermotropic liquid crystal properties is preferred.
[0056] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its kind. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0057] The birefringence Δn of the liquid crystal orientation fixing layer is preferably 0.06 or more, more preferably 0.08 or more, further preferably 0.09 or more, and particularly preferably 0.10 or more. The upper limit of Δn may be, for example, 0.13, or may be, for example, 0.12. When Δn falls within such a range, the desired in-plane delay can be achieved with an extremely small thickness. As a result, the thickness of each of the liquid crystal orientation fixing layer and the optical laminate can be further reduced, and thus can ultimately contribute to the significant thinning of the image display device.
[0058] The liquid crystal orientation fixed layer may exhibit such a reverse wavelength dispersion characteristic, i.e., its retardation value increases with an increase in the wavelength of the measuring light, such a positive wavelength dispersion characteristic, i.e., the retardation value decreases with an increase in the wavelength of the measuring light, or such a flat wavelength dispersion characteristic, i.e., the retardation value remains substantially unchanged even when the wavelength of the measuring light changes.
[0059] The first liquid crystal orientation fixing layer 21 can generally be used as a λ / 2 plate, and the second liquid crystal orientation fixing layer 22 can generally be used as a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal orientation fixing layer is preferably 200nm to 300nm, more preferably 230nm to 290nm, and even more preferably 250nm to 280nm, and the Re(550) of the second liquid crystal orientation fixing layer is preferably 100nm to 200nm, more preferably 120nm to 170nm, and even more preferably 130nm to 150nm. The thickness of the first liquid crystal orientation fixing layer can be adjusted so that the desired in-plane delay of the λ / 2 plate can be obtained. Specifically, the thickness of the layer can be, for example, 2.0μm to 4.0μm. The thickness of the second liquid crystal orientation fixing layer can be adjusted so that the desired in-plane delay of the λ / 4 plate can be obtained. Specifically, the thickness of the layer can be, for example, 1.0μm to 2.5μm. The angle formed by the slow axis of the first liquid crystal orientation fixed layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably 14° to 16°, and the angle formed by the slow axis of the second liquid crystal orientation fixed layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably 74° to 76°. The arrangement order of the first liquid crystal orientation fixed layer and the second liquid crystal orientation fixed layer may be reversed, and the angle formed by the slow axis of the first liquid crystal orientation fixed layer and the absorption axis of the polarizer and the angle formed by the slow axis of the second liquid crystal orientation fixed layer and the absorption axis of the polarizer may be reversed.
[0060] A side chain type thermotropic liquid crystal polymer may be introduced into the first liquid crystal fixed layer and / or the second liquid crystal orientation fixed layer (basically, the liquid crystal composition used to form these layers). When the side chain type thermotropic liquid crystal polymer is introduced, a vertical orientation (vertical orientation) effect on the liquid crystal monomer may occur. As a result, the nz of the first liquid crystal orientation fixed layer and / or the second liquid crystal orientation fixed layer may be made larger, and as a result, the nz coefficient of the first liquid crystal orientation fixed layer and / or the second liquid crystal orientation fixed layer may be set to fall within the above-mentioned desired range. Finally, the Nz coefficient of the retardation layer may be set to fall within the above-mentioned desired range without setting a positive C plate to be described later.
[0061] A copolymer containing a monomer unit having a thermotropic liquid crystal segment side chain and a monomer unit having a non-liquid crystal segment side chain is generally used as a side chain type thermotropic liquid crystal polymer. When the side chain type liquid crystal polymer contains a thermotropic liquid crystal segment in its side chain, the polymer can be oriented when the liquid crystal composition is heated to a predetermined temperature. In addition, when the side chain type liquid crystal polymer contains a non-liquid crystal segment in its side chain, the non-liquid crystal segment interacts with a photopolymerizable liquid crystal monomer, and thus a vertical alignment effect on the photopolymerizable liquid crystal monomer can occur.
[0062] A copolymer containing a liquid crystal monomer unit represented by the general formula (I) and a non-liquid crystal monomer unit represented by the general formula (II) is preferably used as the side chain type thermotropic liquid crystal polymer.
[0063]
[0064] In formula (I), R 1 represents a hydrogen atom or a methyl group, R 2 represents a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms or an alkyl group having 1 to 6 carbon atoms, and X 1 "a" represents an integer of 1 to 6, and "b" and "c" each independently represent 1 or 2.
[0065] In formula (II), R 3 represents a hydrogen atom or a methyl group, and R 4 represents an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms or a group represented by the following general formula (III).
[0066]
[0067] In formula (III), R 5 represents an alkyl group having 1 to 5 carbon atoms, and "d" represents an integer of 1 to 6.
[0068] The ratio between the liquid crystal monomer unit and the non-liquid crystal monomer unit in the side chain type liquid crystal polymer can be appropriately set according to the purpose. The (molar ratio) of the non-liquid crystal monomer to the liquid crystal monomer unit and the non-liquid crystal monomer unit is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and even more preferably 0.15 to 0.5. Through this structure, a liquid crystal orientation fixing layer showing a desired refractive index characteristic (Nz coefficient) can be obtained.
[0069] The ratio between the liquid crystal monomer and the side chain type liquid crystal polymer in the liquid crystal composition can be appropriately set according to the purpose. When the content of the side chain type liquid crystal polymer is large, the Nz coefficient tends to decrease, and when the content of the liquid crystal monomer is large, the Nz coefficient tends to increase. Relative to the content of the side chain type liquid crystal polymer, the content of the liquid crystal monomer is preferably 1.2 times to 20 times, more preferably 1.3 times to 10 times, still more preferably 1.4 times to 9 times, particularly preferably 1.5 times to 8 times. Through this structure, it is possible to obtain a liquid crystal orientation fixing layer showing a desired refractive index characteristic (Nz coefficient).
[0070] Details on the side chain type liquid crystal polymer and a method of forming a liquid crystal alignment fixing layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921, the description of which is incorporated herein by reference.
[0071] The retardation layer 20 may also include a positive C plate. The positive C plate generally has a refractive index characteristic showing a relationship of nz>nx=ny. The thickness direction retardation Rth(550) of the positive C plate is preferably -50nm to -300nm, more preferably -70nm to -250nm, still more preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx=ny" includes not only the case where nx and ny are exactly equal to each other, but also the case where nx and ny are substantially equal to each other. That is, the in-plane retardation Re(550) of the positive C plate can be less than 10nm.
[0072] The positive C plate can be formed by using, for example, a composition containing the above-mentioned side chain type liquid crystal polymer. A method of forming the positive C plate is specifically, for example, a method described in Japanese Patent Application Publication No. 2002-333642. In this case, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and still more preferably 0.5 μm to 5 μm.
[0073] D. Base material
[0074] As described above, the tensile elastic modulus of the substrate 40 is 3,000 N / mm 2or greater. With this configuration, peeling defects when peeling the substrate can be suppressed. Specifically, the second liquid crystal orientation fixing layer can be prevented or satisfactorily suppressed from peeling together with the substrate. The tensile elastic modulus of the substrate is preferably 4,000 N / mm 2 or more, more preferably 5,000 N / mm 2 or more, still more preferably 6,000 N / mm 2 or more, particularly preferably 6,500 N / mm 2 At the same time, the tensile elastic modulus of the substrate can be, for example, 9,000 N / mm 2 or less, or may be, for example, 8,500 N / mm 2 The tensile elastic modulus can be measured according to JIS K 7161.
[0075] The peel strength of the substrate 40 is preferably 1.2N / 50mm or less, more preferably 1.0N / 50mm or less, still more preferably 0.8N / 50mm or less, and particularly preferably 0.7N / 50mm or less. At the same time, the peel strength of the substrate may be, for example, 0.1N / 50mm or more, or may be, for example, 0.2N / 50mm or more. With this structure, it is possible to suppress peeling defects when peeling the substrate in the same manner as when the tensile elastic modulus is set to a predetermined value or more. Specifically, it is possible to prevent or satisfactorily suppress the second liquid crystal orientation fixing layer from peeling off together with the substrate.
[0076] As mentioned above, the substrate is an orientation substrate for the second liquid crystal orientation fixing layer, and therefore has an orientation regulating force. The orientation regulating force can usually be applied by rubbing orientation, stretching substrate orientation or light orientation. Among them, stretching substrate orientation or light orientation is preferred.
[0077] As long as the above-mentioned required tensile modulus is obtained, any suitable configuration can be adopted to substrate.Specifically, substrate can be a single film or can have a laminated structure (can be a stack) of two or more layers.Substrate is usually formed by resin film.Therefore, substrate can be a single film of resin film, or can be a stack comprising the first resin film and the second resin film.Single film can be excellent in cost and general properties.When a single film can not satisfy required orientation regulating power and required tensile modulus simultaneously, these characteristics can be supplemented and satisfied simultaneously with the stack of multiple resin films.Stack can be a stack further comprising three layers of the 3rd resin film, can be a stack further comprising four layers of the 4th resin film, or can be a stack of five or more layers.Each resin film in the stack is usually laminated by a pressure-sensitive adhesive layer.Stack preferably has the structure of "first resin film / pressure-sensitive adhesive layer / second resin film with orientation regulating power".
[0078] Typical examples of materials for forming the resin film include: cellulose resins such as TAC; cycloolefin resins such as polynorbornene; (meth) acrylic resins; polyester-based resins such as PET and PEN; polyolefin resins such as polyethylene and polypropylene; and polycarbonate resins. The specific structure of the substrate is preferably a single-layer film such as a TAC film with orientation regulating power, or a laminate having a "TAC film with orientation regulating power / pressure-sensitive adhesive layer / PET film" configuration.
[0079] The thickness of the substrate can be changed according to, for example, the material of the substrate or the structure of the substrate. The thickness of the substrate can be, for example, 75 μm or more, can be, for example, 77 μm or more, can be, for example, 80 μm or more, can be, for example, 85 μm or more, or can be, for example, 88 μm or more. At the same time, the thickness of the substrate can be, for example, 120 μm or less, can be, for example, 110 μm or less, or can be, for example, 100 μm or less.
[0080] E. First Adhesive Layer
[0081] The adhesive that can form the first adhesive layer 30 is generally, for example, an active energy ray-curable adhesive. When an active energy ray-curable adhesive is used as the first adhesive layer, the first adhesive layer can be thinned, and as a result, an optical laminate with excellent bending properties can be obtained. In addition, the refractive index of the first adhesive layer can be increased, so the difference in the refractive index of the first adhesive layer and the first liquid crystal orientation fixing layer adjacent thereto can be reduced. As a result, the reflection at the interface between the first adhesive layer and the first liquid crystal orientation fixing layer is suppressed, so an optical laminate with excellent anti-reflection properties can be obtained. As an active energy ray-curable adhesive, for example, a free radical curable type, a cationic curable type or an anionic curable type can be selected as required, and a combination thereof, such as a mixture of a free radical curable type and a cationic curable type, can be appropriately used. An example of a free radical curable adhesive is an adhesive comprising a compound (e.g., a monomer and / or an oligomer) having a free radical polymerizable group (such as a (meth) acrylate group or a (meth) acrylamide group) as a curing component. As active energy ray curing adhesive, the active energy ray curing adhesive with desired characteristics (e.g., storage elastic modulus after curing) can be obtained by adjusting the type, combination and blending ratio of monomers and / or oligomers, crosslinking agents, etc. with double bonds. Examples of active energy rays include UV light, visible light, infrared rays and electron beams. Preferably, UV curable adhesives. This is because UV curable adhesives have excellent general properties and operability. Active energy ray curing adhesives are well known in the art, so a detailed description of their structure is omitted.
[0082] In this case, the thickness of the third retardation layer is preferably 0.5 μm to 3.0 μm, more preferably 0.5 μm to 2.0 μm, and still more preferably 0.5 μm to 1.5 μm. When such a thickness is adopted, thinning of the optical laminate can be facilitated.
[0083] F. Second adhesive layer
[0084] The second adhesive layer 25 may be formed of any suitable adhesive. The thickness of the second adhesive layer is preferably 0.1 μm to 3.0 μm, more preferably 0.5 μm to 2.0 μm, and even more preferably 0.8 μm to 1.5 μm. When such a thickness is adopted, it can help to thin the optical laminate in the same manner as in the first adhesive layer.
[0085] Example
[0086] The present invention is specifically described below by way of examples. However, the present invention is not limited to these examples. The measurement methods and evaluation methods in the examples are as follows.
[0087] (1) In-plane retardation Re(550), thickness retardation rth(550), and Nz coefficient
[0088] Re(550) and Rth(550) were measured using "AxoScan" manufactured by Axometrics, Inc. The Nz coefficient was calculated from Rth / Re.
[0089] (2) Tensile elastic modulus
[0090] The tensile modulus of elasticity of the substrate used in Examples and Comparative Examples was measured by performing a tensile test in accordance with JIS K7161.
[0091] (3) Peel strength
[0092] The measurement was performed in accordance with JIS Z 0237. The specific steps are as follows: the optical laminate obtained in each of the examples and comparative examples was cut into a piece having a length of 150 mm and a width of 50 mm to provide a measurement sample; the peel strength when the substrate was peeled off from the measurement sample was measured using a tensile tester (manufactured by Tester Sangyo Co., Ltd., product name "TE-702 High-Speed Peel Tester"), with a peeling angle of 90° and a peeling rate of 15,000 mm / min.
[0093] (4) Stripping assessment
[0094] The presence or absence of peeling defects when peeling the substrate from the optical layered bodies obtained in Examples and Comparative Examples was observed while the optical layered bodies were being rolled, and the peeling was evaluated according to the following criteria.
[0095] Satisfactory: The substrate can be peeled off individually satisfactorily.
[0096] Poor: The second liquid crystal alignment fixing layer was peeled off together with the substrate.
[0097] [Example 1]
[0098] 1. Production of polarizers
[0099] 1-1. Production of polarizers
[0100] An amorphous isophthalic acid copolymerized polyethylene terephthalate film (thickness: 100 μm) having an elongated shape and having a Tg of about 75° C. was used as a thermoplastic resin substrate, and one surface of the resin substrate was subjected to a corona treatment.
[0101] A PVA aqueous solution (coating liquid) was prepared by dissolving a product obtained by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree: 4,200, saponification degree: 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name: "GOHSEFIMER") in water.
[0102] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm. Thus, a laminate was produced.
[0103] The obtained laminate was uniaxially stretched at a ratio of 2.4 times in its longitudinal direction (length direction) in an oven at 130° C. (auxiliary stretching treatment in air).
[0104] Next, the laminated body was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 100 parts by weight of water with 4 parts by weight of boric acid) having a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0105] Next, the laminate is immersed in a dyeing bath (an aqueous solution of iodine obtained by blending 100 parts by weight of water with iodine and potassium iodide in a weight ratio of 1:7) having a liquid temperature of 30°C for 60 seconds, while adjusting the concentration of the aqueous solution so that the single-layer transmittance (Ts) of the polarizer finally obtained becomes the desired value (dyeing treatment).
[0106] Next, the laminate was immersed in a crosslinking bath (boric acid aqueous solution obtained by blending 100 parts by weight of water with 3 parts by weight of potassium iodide and 5 parts by weight of boric acid) having a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0107] Thereafter, while the stack is immersed in an aqueous boric acid solution at a liquid temperature of 70°C (boric acid concentration: 4 wt%, potassium iodide concentration: 5 wt%), the stack is uniaxially stretched in the longitudinal direction (length direction) between rollers with different circumferential speeds so that the total stretching ratio becomes 5.5 times (underwater stretching treatment).
[0108] Thereafter, the laminated body was immersed in a washing bath (an aqueous solution obtained by blending 100 parts by weight of water with 4 parts by weight of potassium iodide) having a liquid temperature of 20° C. (washing treatment).
[0109] Thereafter, the laminate was dried in an oven maintained at approximately 90°C while being brought into contact with a heating roller made of SUS whose surface temperature was maintained at approximately 75°C (drying shrinkage treatment).
[0110] Thus, a polarizing plate having a thickness of about 5 μm was formed on the resin substrate to provide a polarizer having a “resin substrate / polarizing plate” configuration. The single-layer transmittance Ts of the polarizer was 43.3%.
[0111] 1-2. Production of polarizing film
[0112] The HC-TAC film was bonded to the surface of the obtained polarizer (the surface opposite to the resin substrate) by a UV-curable adhesive. The HC-TAC film is a film obtained by forming an HC layer (thickness: 7 μm) on a triacetyl cellulose (TAC) film (thickness: 25 μm), and bonded so that the TAC film is on the polarizer side. Next, the resin substrate was peeled off, and a TAC film (thickness: 25 μm) was bonded to the peeled surface by a UV-curable adhesive. Thus, a polarizing plate having a "HC layer / TAC film (protective layer) / polarizer / TAC film (protective layer)" configuration was obtained.
[0113] 2. Production of delay layer
[0114] A photopolymerizable liquid crystal compound showing a nematic liquid crystal phase (manufactured by BASF SE, "Paliocolor LC242", chemical formula indicated below) was dissolved in cyclopentanone to prepare a solution having a solid content concentration of 20 wt%. A leveling agent (manufactured by DIC, "MEGAFACE F-563"), a photopolymerization initiator (manufactured by IGM Resins BV, "Omnirad 907"), and a crosslinking agent (manufactured by Nakamura Shinkagaku Kogyo Co., Ltd., "A-DCP") were added to the solution to prepare a coating liquid for forming a liquid crystal orientation fixing layer. A TAC film (thickness: 80 μm, tensile elastic modulus: 3,391 N / mm 2) as a substrate. The above coating solution for forming a liquid crystal orientation fixing layer was applied to the substrate using a spin coater and heated at 100° C. for 3 minutes to align the liquid crystal compound. The resultant was cooled to room temperature and then subjected to a nitrogen atmosphere with an integrated light intensity of 600 mJ / cm 2 The UV light was irradiated and photocured to fix the orientation state of the liquid crystal compound. Thus, a laminate having a structure of "substrate / first liquid crystal orientation fixing layer" (thickness: 2 μm, Re (550): 270 nm) was obtained. A laminate having a structure of "substrate / second liquid crystal orientation fixing layer" (thickness: 1 μm, Re (550): 140) was obtained in the same manner as above except that the coating thickness was changed.
[0115]
[0116] 3. Production of positive C-plate
[0117] 20 parts by weight of a side chain type liquid crystal polymer represented by the chemical formula indicated below having a weight average molecular weight of 5,000 (n=0.35, and for convenience, the polymer is represented in the form of a block polymer), 80 parts by weight of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF SE, product name: Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals, product name: Irgacure 907) were dissolved in 200 parts by weight of cyclopentanone to prepare a liquid crystal coating liquid. Then, the coating liquid was applied to a PET substrate that had been subjected to a vertical alignment treatment using a rod coater, and then heated and dried at 80°C for 4 minutes to orient its liquid crystal molecules. UV light was applied to the liquid crystal layer to cure the liquid crystal layer. Thus, a positive C plate (thickness: 3 μm) was formed on the substrate.
[0118]
[0119] 4. Manufacturing of optical laminates
[0120] The first liquid crystal orientation fixing layer is bonded to the TAC film surface of the polarizer opposite to the HC layer via a UV-curable adhesive (thickness: 1 μm), and then the substrate is peeled off. Next, the positive C plate is transferred to the surface of the first liquid crystal orientation fixing layer via a UV-curable adhesive (thickness: 1 μm). In addition, the second liquid crystal orientation fixing layer is bonded to the surface of the positive C plate via a UV-curable adhesive (thickness: 1 μm). Thus, an optical laminate having a "polarizer / delay layer / substrate" structure is obtained. The Re (550) of the delay layer as a whole is 168 nm, and its Nz coefficient is 0.52. The peel strength when peeling the substrate from the obtained optical laminate and the presence or absence of peeling defects are evaluated. The results are shown in Table 1.
[0121] [Example 2]
[0122] In addition to using another TAC film (thickness: 80 μm, tensile elastic modulus: 8,147 N / mm 2 ) as the substrate, an optical layered body was produced in the same manner as in Example 1. The obtained optical layered body was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0123] [Example 3]
[0124] An optical laminate was prepared in the same manner as in Example 1 except that a laminate having a configuration of "TAC film (thickness: 40 μm) / pressure-sensitive adhesive layer (thickness: 10 μm) / PET film (thickness: 38 μm)" was used as a substrate. The substrate was produced by bonding a surface protection film (product name: "RP1010M") manufactured by Nitto Denko Corporation to the TAC film. The tensile elastic modulus of the substrate was 7,143 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0125] [Example 4]
[0126] An optical laminate was prepared in the same manner as in Example 1 except that a laminate having a configuration of "TAC film (thickness: 40 μm) / pressure-sensitive adhesive layer (thickness: 10 μm) / PET film (thickness: 38 μm)" was used as a substrate. The substrate was produced by bonding a surface protection film (product name: "RP109F") manufactured by NittoDenko Corporation to the TAC film. The tensile elastic modulus of the substrate was 6,901 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0127] [Example 5]
[0128] An optical laminate was prepared in the same manner as in Example 1 except that a laminate having a configuration of "TAC film (thickness: 40 μm) / pressure-sensitive adhesive layer (thickness: 20 μm)" was used as a substrate. The substrate was produced by bonding a surface protective film (product name: "HP300") manufactured by Nitto Denko Corporation to the TAC film. The tensile elastic modulus of the substrate was 4,079 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0129] [Comparative Example 1]
[0130] In addition to using another TAC film (thickness: 40 μm, tensile elastic modulus: 2,021 N / mm 2) as the substrate, an optical layered body was produced in the same manner as in Example 1. The obtained optical layered body was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0131] [Comparative Example 2]
[0132] An optical laminate was prepared in the same manner as in Example 1 except that a laminate having a configuration of "TAC film (thickness: 40 μm) / pressure-sensitive adhesive layer (thickness: 20 μm)" was used as a substrate. The substrate was produced by bonding a self-adhesive surface protection film (product name: "TORETEC", manufactured by Toray Industries, Inc.) to the TAC film. The tensile elastic modulus of the substrate was 2,376 N / mm 2 The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0133] Table 1
[0134]
[0135] The optical laminate according to at least one embodiment of the present invention can be suitably used in an image display device (typically a liquid crystal display device or an organic EL display device).
Claims
1. An optical laminate, comprising: A polarizing plate including a polarizer; And A retardation layer laminated on the polarizing plate via a first adhesive layer; And A substrate laminated on the retardation layer in a peelable manner; Wherein the retardation layer sequentially includes from the polarizing plate side: A first liquid crystal alignment fixing layer; and A second liquid crystal alignment fixing layer laminated on the first liquid crystal alignment fixing layer via a second adhesive layer; Wherein the retardation layer has one of a circular polarization function or an elliptical polarization function, a relationship of Re(450) < Re(550) < Re(650), and an Nz coefficient of 0.30 to 0.70 as a whole, and The substrate is an alignment substrate for the second liquid crystal alignment fixing layer and has a strength of 3,000 N / mm 2 or greater tensile modulus of elasticity.
2. The optical layered body according to claim 1, wherein: The substrate has a thickness of 75 μm or more.
3. The optical laminate according to claim 2, wherein: The substrate is a single-layer film.
4. The optical layered body according to claim 2, wherein: The substrate has a laminate structure of two or more layers.
5. The optical laminate according to any one of claims 1-4, in, The polarizing plate further includes protective layers provided on both sides of the polarizer, and Wherein the polarizing plate has a thickness of 100 μm or less.
6. The optical layered body according to any one of claims 1 to 4, wherein The total thickness from the polarizing plate to the second liquid crystal alignment fixing layer is 110 μm or less.
7. The optical layered body according to any one of claims 1 to 4, wherein The first adhesive layer is formed of an adhesives curable by UV.
Citation Information
Patent Citations
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2
Liquid crystalline copolymer
GB2280445A
Optically active liquid crystal compound having cyano group
JP1989070455A